2016
DOI: 10.4236/jss.2016.45019
|View full text |Cite
|
Sign up to set email alerts
|

Where Is Nepal in the Demographic Transition within the Wider Context of the Nutrition Transition?

Abstract: Historically, the process of nutrition transition begins with the shifts in demographic transition, moving away from high to low mortality, high to low fertility, high percentage of young population to high proportion of elderly population, high to low population growth rate; and short to long life expectancy at birth. The objective is to identify where Nepal is in demographic transition and whether demographic transition is considered as one of the proximate covariates of nutrition transition. Nepal's positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…One of the previous studies concluded that Nepal's dietary policies are not aligned with the country's disease situation [ 32 ]. Per-capita energy consumption and sugar and sweeteners consumption have witnessed a significant rise in the past few decades [ 33 ], which could be the result of ineffective policy initiatives to promote a healthy diet to address the increased burden of NCDs including CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the previous studies concluded that Nepal's dietary policies are not aligned with the country's disease situation [ 32 ]. Per-capita energy consumption and sugar and sweeteners consumption have witnessed a significant rise in the past few decades [ 33 ], which could be the result of ineffective policy initiatives to promote a healthy diet to address the increased burden of NCDs including CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Nepalese have cereal-based dietary food habits and rice contributes basics of cereal requirements. It is a fundamental source of carbohydrates (Subedi et al 2017), according to National Living Standard Survey NLSS (2011), the consumption of milled rice was 122 kg person -1 year -1 out of 191 kg of total cereals consumed per year. It also provides livelihoods for 65% of the population engaged in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major causes of obesity identified worldwide is the sedentary lifestyle and fat-and sugar-laden diets (Vaidya et al, 2010). Moreover, the Nepalese diet has shifted from agricultural staple foods to modern processed foods with higher energy, fat, and sugar (Subedi et al, 2017). Children under two in Nepal get a quarter of their calories from junk foods that usually have high sugar, salt, and fat content (Pries et al, 2016).…”
Section: Introductionmentioning
confidence: 99%